Pengaruh Latihan Tangan dengan Media Squishy terhadap Kekuatan Genggam pada Lansia - Ela Susilawati; Adis Nadila; Kamaluddin Latief (Faletehan Health Journal, 2023)
The aging process causes a decrease in musculoskeletal function, causing elders suffer from muscle and joint stiffness. Hand exercise with squishy is proven to be able to prevent from loss of muscle strength. The purpose of this research was to determine the effects of hand exercise with squishy on the grip strength of elders. It was a quasy experimental study and the design was pretest and posttest with control group. The size of samples were 60 elders; 30 elders joined the intervention group and the rest 30 joined the control group. The instrument of measuring grip strength was hand dynamometer and the data was analyzed by Wilcoxon test. The results showed females in the intervention group were significantly influenced with p value 0.004 <0.05. Meanwhile, males in the intervention group showed the grip strength of right hand with p value 0.209 >0.05 which means that there was no effect. The researcher concluded that there are no effects of hand exercise with squishy on the grip strength of elders. Further studies should focus on the grip strength levels of elders in order to determine the effect ratio of hand exercise with squishy.